Aerosol exposure enhanced infection of low pathogenic avian influenza viruses in chickens. Issue 1 (2nd November 2018) - Jegede, Akinlolu; Fu, Qigao; Lin, Min; Kumar, Ashok; Guan, Jiewen
Abstract: To assess the impact of different routes of inoculation on experimental infection of avian influenza (AI) viruses in chickens, this study compared virus replication and cytokine gene expression in respiratory and gastrointestinal organ tissues of chickens, which were inoculated with four low pathogenic subtypes, H6N1, H10N7, H10N8, and H13N6 AI viruses via the aerosol, intranasal, and oral routes respectively. Aerosol inoculation with the H6N1, H10N7, and H10N8 viruses significantly increased viral titres and upregulated the interferon (IFN)‐γ, interleukin (IL)‐6, and IL‐1β genes in the trachea and lung tissues compared to intranasal or oral inoculation. Furthermore, one or two out of six chickens died following exposure to aerosolized H6N1 or H10N8 virus respectively. The H13N6 virus reached the lung via aerosol inoculation although failed to establish infection. Collectively, chickens were more susceptible to aerosolized AI viruses compared to intranasal or oral inoculation, and virus aerosols might post a significant threat to poultry health.